Bicyclo[10.2.1]pentadecenone derivatives by free radical macrocyclisation - Robertson, J; Burrows, J; Stupple, P (1997)
The synthesis of intermediates for the preparation of stereoisomeric bicyclo[10.2.1]pentadec-13-en-3-ones is described. The preparation and the addition of 6-functionalised hexylcuprate reagents to bicyclic lactone 5 is discussed and a method described for the epimerisation of the so-formed trans-disubstituted cyclopentene derivatives. The cis- and trans-1,4-disubstituted cyclopentenes are both shown to undergo 13-endo-trig cyclisation affording the title bicyclic compounds in moderate yield.